Catalytic deoxygenation on transition metal carbide catalysts. Issue 3 (20th January 2016) - Sullivan, Mark M.; Chen, Cha-Jung; Bhan, Aditya
Abstract : We highlight the evolution and tunability of catalytic function of transition metal carbides under oxidative and reductive environments for selective deoxygenation reactions. Abstract : We discuss the evolution of catalytic function of interstitial transition metal formulations as a result of bulk and surface structure modifications via alteration of synthesis and reaction conditions, specifically, in the context of catalytic deoxygenation reactions. We compare and contrast synthesis techniques of molybdenum and tungsten carbides, including temperature programmed reaction and ultra-high vacuum methods, and note that stoichiometric reactions may occur on phase-pure materials and that in situ surface modification during deoxygenation likely results in the formation of oxycarbides. We surmise that catalytic metal–acid bifunctionality of transition metal carbides can be tuned via oxygen modification due to the inherent oxophilicity of these materials, and we demonstrate the use of in situ chemical titration methods to assess catalytic site requirements on these formulations.